2018
DOI: 10.1049/iet-pel.2018.5336
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐frequency induction heating for gear hardening: converter, resonant circuit, and FEM modelling

Abstract: In order to achieve required mechanical properties of hardened elements, such as gear wheels, dual-frequency induction heating may be used. Dual-frequency allows heating only the outline of the gear, due to mixed penetration depth of the subject frequencies. This method of hardening requires the process to be very short as heat may spread by means of conduction. This study presents a 3 kW prototype inverter and its control scheme is used to generate dual-frequency output current. The overall efficiency of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Patents resulting from the work reported in this manuscript [25,26]. Author Contributions: Conceptualization, K.F.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patents resulting from the work reported in this manuscript [25,26]. Author Contributions: Conceptualization, K.F.…”
Section: Discussionmentioning
confidence: 99%
“…Two inverter topologies are proposed. The following designations of 2T1C [25] and 3T [26] are adopted in this paper. The 2T1C topology shown in Figure 3 contains two transistor branches (2T) and one common capacitor branch (1C), which can be used to eliminate the DC component.…”
Section: Proposed Dual-frequency Inverter Topologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] Tong et al improved the numerical model by introducing an additional plastic strain model for application in spur gear's asynchronous‐dual frequency induction hardening. [ 15 ] The insights of numerical simulation preparation in dual‐frequency induction heating along gear tooth profile were presented by Kierepka et al [ 16 ] More simulation works in dual‐frequency in achieving the uniformity of temperature distribution in bevel gear were can be studied in the recent works of Zhao et al [ 17 ] Wang et al showed exciting works in the scanning induction hardening simulation and the effect of scanning speed by incorporating commercial software. [ 18 ] Zhong et al showed an improved model by considering martensite transformation plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…A higher efficiency for induction hardening could be achieved using a particular test setup, with an approach relying on efficiency maximization, leading to an efficiency of up to 91% [35]. An efficiency above 95% is reserved for low-temperature applications, where even 97% efficiency is achievable [36]. However, in induction hardening, only special systems like dual-frequency induction heating (efficiency of the inverter up to 96%) [37] can reach the goal.…”
mentioning
confidence: 99%